PROSINDES-UNDARMA KUPANG TOWARDS WHITE PAPER ONE MAP POLICY BEYOND 2024 THROUGH RURALIZATION OF MILLENNIAL ENTREPRENEURS IN THE ERA OF SOCIETY 5.0 IN 3,442 VILLAGES IN EAST NUSA TENGGARA, INDONESIA - Daniel H Wadu; Jidon A Y Nubatonis; Pither Y Boimau; Magda Silfia Yeni Laka; Rola M. Sakan; Linros S N Tanu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explains the implementation of the ProSIndes - Undarma millennial entrepreneurship program in 3,442 villages in East Nusa Tenggara (NTT), aiming to encourage rural entrepreneurship and its contribution to the *One Map Policy* and Society 5.0. The innovation adoption process is analyzed using a mixed-method descriptive-evaluative approach based on Rogers' Diffusion of Innovation Theory. The results show a wide range of implementation with variations in penetration, influenced by innovation characteristics, communication channels, social systems, and adopter categories, and impact increasing millennial entrepreneur participation and digital literacy. The success of ProSIndes-Undarma Kupang shows that building Indonesia from the village is not just rhetoric but can be realized through a contextual, applicable, and collaboration-based higher education strategy. With these achievements, ProSIndes-Undarma Kupang has become not just an academic program but a grassroots development movement that answers Indonesia's current and future challenges. This program demonstrates that through village-oriented education, Indonesia can accelerate the leap of civilization towards an intelligent, independent, and socially just society, as the ideals of Society 5.0 and the vision of Golden Indonesia 2045.